2015
DOI: 10.3758/s13415-015-0384-1
|View full text |Cite
|
Sign up to set email alerts
|

The neural circuitry supporting goal maintenance during cognitive control: a comparison of expectancy AX-CPT and dot probe expectancy paradigms

Abstract: Goal maintenance is an aspect of cognitive control that has been identified as critical for understanding psychopathology according to criteria of the NIMH-sponsored CNTRICS (Cognitive Neuroscience Treatment Research to Improve Cognition in Schizophrenia) and Research Domain Criteria (RDoC) initiatives. CNTRICS proposed the expectancy AX-CPT, and its visual-spatial parallel the dot probe expectancy (DPX), as valid measures of the cognitive and neural processes thought to be relevant for goal maintenance. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 42 publications
(83 reference statements)
9
55
0
Order By: Relevance
“…Research on Cognitive Systems has been considerable and diverse, with eighteen studies published on four of the six constructs within the domain (e.g., Cognitive Control: Lopez-Garcia et al (2016); Perception: Silverstein et al (2015); Attention: Kleinman et al (2015); and Working Memory: Francazio and Flessner (2015)). To elaborate on one example, Chan et al (2015) demonstrated how a standard performance-monitoring event-related potential paradigm can be used within an RDoC framework to examine Cognitive Control and Performance Monitoring systems.…”
Section: Resultsmentioning
confidence: 99%
“…Research on Cognitive Systems has been considerable and diverse, with eighteen studies published on four of the six constructs within the domain (e.g., Cognitive Control: Lopez-Garcia et al (2016); Perception: Silverstein et al (2015); Attention: Kleinman et al (2015); and Working Memory: Francazio and Flessner (2015)). To elaborate on one example, Chan et al (2015) demonstrated how a standard performance-monitoring event-related potential paradigm can be used within an RDoC framework to examine Cognitive Control and Performance Monitoring systems.…”
Section: Resultsmentioning
confidence: 99%
“…Second, behavioral results indicated that similar relationships existed between both A and B cue RT with an independent measure of working memory, suggesting that both cues utilized proactive cognitive control to some degree. Finally, variations in task design (e.g., longer inter‐stimulus intervals, differences in the frequency of BX probes) also influence how participants utilize cue information (Lesh et al, ; Lopez‐Garcia et al, ) and may ultimately alter DLPFC recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a significant inverse relationship was found between differential cuerelated activation in the default mode network (DMN) and only the L Cblm. Asterisks denote significant relationships information (Lesh et al, 2013;Lopez-Garcia et al, 2016) and may ultimately alter DLPFC recruitment.…”
Section: Both Probes Followingmentioning
confidence: 99%
“…Collectively, these data indicate that reduced PC DAT functioning drives impaired attentional performance of participants with BD mania, and also possibly children with ADHD. Given the importance of parietal function across CPTs, it is also possible that altered PC function negatively impacts other disorders such as schizophrenia or additional phases of BD such as depression. Future studies should address this limitation and include other populations and phases of BD illness.…”
Section: Discussionmentioning
confidence: 99%
“…69 Collectively, these data indicate that reduced PC DAT functioning drives impaired attentional performance of participants with BD mania, and also possibly children with ADHD. Given the importance of parietal function across CPTs, 70 Several limitations exist within these studies. One is that while the majority of people with BD tested were female, the mice tested were only male.…”
Section: Bd Mania Patients Exhibited a Similar Profile Of Poor Attentionmentioning
confidence: 99%